IDENTIFIKASI FITOKIMIA, UJI TOKSISITAS DAN UJI ANTIOKSIDAN EKSTRAK ETANOL DAUN TANJUNG (Mimusops elengi L.) - Asma, Nur; Mellyanti, Ayu; Akbar, Akbar; Erwin, Erwin (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Tanjung Leaf (Mimusops elengi L.) is a type of plant that originates from India, but its habitat has spread throughout Indonesia. Tanjung leaves are traditionally used by the community to treat various diseases such as ulcers, worms, fever, inflammation and cancer so research on this plant is very interesting to study and analyze regarding its chemical compound content. The aim of this research was to determine the secondary metabolite content contained in Tanjung Leaves, measure the level of toxicity and antioxidant level of the ethanol extract of Tanjung Leaves (Mimusops elengi L.). The methods used in this research were extraction, phytochemical test, toxicity test using the Brine Shrimp Lethality Test (BSLT) method, and antioxidant activity test using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The results of phytochemical tests show that the ethanol extract of Tanjung Leaves (Mimusops elengi L.) contains alkaloids, triterpenoids, phenolics, flavonoids, saponins and quinones. Based on the results of the toxicity test, it shows that the ethanol extract of Daun Tanjung (Mimusops elengi L.) has a toxicity level of 80.0571 ppm in the toxic category (<1000 ppm) so it can be concluded that the ethanol extract of Daun Tanjung (Mimusops elengi L.) has bioactivity because is toxic to Artemia salina L. shrimp larvae. Furthermore, based on antioxidant activity tests, it shows that the ethanol extract of Tanjung Leaves (Mimusops elengi L.) has an IC50 value of 11.02 ppm in the very strong category (<50 ppm). Based on these results, it can be concluded that the ethanol extract of Tanjung Leaves (Mimusops elengi L.) has antioxidant properties in warding off free radicals. Keywords: Antioxidants, Phytochemicals, Secondary Metabolites, Tanjung Leaves, Toxicity